Can a cash crop be a women’s crop?: Examining gender norms, relations and equity around lentil commercialization in Ethiopia - Nomunume Baada, Jemima; Najjar, Dina; Seifu, Mahelet Hailemariam (Elsevier, 2023)
The benefits of subsistence-crop commercialization may depend on gender norms and relations. In sub-Saharan Africa, crop commercialization has been shown to often have unequal outcomes for women and men due to pre-existing social hierarchies and norms around farm roles, asset ownership, control over crops and income, and local farming practices. Using qualitative methods, this article examines gender norms and relations around lentil commercialization in the Amhara and Oromia regions of Ethiopia, to understand whether the benefits of market-orientated lentil production accrue to women and men farmers equitably. The findings reveal that despite naming lentils a women’s crop, women remain marginalized from the sale and use of lentil. The study also found that lentil commercialization is often accompanied by labour commercialization, which has exclusionary effects on farmers of low socioeconomic status and unmarried women. Some policy recommendations are suggested based on these findings.